Pendekatan Restorative Justice terhadap Penyelesaian Penganiayaan Ringan di Polresta Jambi Perspektif Hukum Pidana Islam: Restorative Justice Approach towards Resolving Mild Assault in Jambi Police Office Islamic Criminal Law Perspective - Pauziah, Pauziah; Bahrul Ma’ani; Siti Marlina (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2025)
Petty mistreatment is still a challenge in Indonesia's criminal system, especially because its resolution through litigation often does not provide a sense of justice for both victims and perpetrators. Restorative justice offers an alternative approach that emphasizes victim recovery, perpetrator responsibility, and social harmony. This study analyzes the application of restorative justice in cases of minor persecution in the Jambi Police and reviews it from the perspective of Islamic criminal law. The research uses empirical juridical methods and qualitative approaches. The results of the study found that the implementation of restorative justice still faces obstacles, such as low public understanding, lack of coordination between law enforcement, and suboptimal regulations. In Islamic criminal law, this approach is in line with the principles of diat and takzir which prioritize peaceful settlement and substantive justice. This research is expected to contribute to encouraging the strengthening of regulations, public education, and synergy between agencies for the effectiveness of the implementation of restorative justice in cases of minor persecution.